2009
DOI: 10.1007/s10397-009-0533-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of a pelvic retroperitoneal leiomyoma—case report

Abstract: Leiomyomas are benign tumors frequently found in the fourth and fifth decades of life. Although the uterus is the most common site of origin of leiomyomas, they can develop at any site where there is smooth muscle cell. Extrauterine leiomyomas are not common and usually their diagnostic are more challenging. In this paper, we report one case of pelvic retroperitoneal leiomyoma associated to vulvar/perineal leiomyomas. A 47-year-old female patient presented with a 6-month history of deep dyspareunia, abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…So the approach of operation was selected to the open method for the purpose of radical resection of the tumor. The laparoscopic approach is the feasible method in the treatment of retroperitoneal leiomyoma 11 and the more accurate diagnosis might be possible to consider the laparoscopic approach in our case.…”
Section: Discussionmentioning
confidence: 90%
“…So the approach of operation was selected to the open method for the purpose of radical resection of the tumor. The laparoscopic approach is the feasible method in the treatment of retroperitoneal leiomyoma 11 and the more accurate diagnosis might be possible to consider the laparoscopic approach in our case.…”
Section: Discussionmentioning
confidence: 90%
“…Main stay of treatment is surgical removal of the mass which can be done by laparotomy or laparoscopy. Kondo et al [5] reported a case of retroperitoneal fibroid where resection was done by laparoscopic approach. Hysterectomy may be considered depending on the presence of symptomatic fibroids in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…A laparoscopic approach was described in only two cases [ 1 ]. The difficulty with laparoscopic or robot-assisted approaches is related mainly to the relatively large tumor size at diagnosis and the adherence to adjacent structures [ 14 ]. The principal aim is to ensure a one-piece excision of the tumor and to conserve the integrity of the surrounding organs and large vessels [ 15 ].…”
Section: Discussionmentioning
confidence: 99%